University teachers’ perceptions of appropriate emotion display and high-quality teacher-student relationship: Similarities and differences across cultural-educational contexts - Hagenauer, Gerda; Gläser-Zikuda, Michaela; Volet, Simone (Frontline Learning Research, 2016)
Research on teachers’ emotion display and the quality of the teacher-student relationship in higher education is increasingly significant in the context of rapidly developing internationalization in higher education, with scholars (and students) moving across countries for research and teaching. However, there is little theoretically grounded empirical research in this area, and the different research strands remain relatively unconnected. The present study aimed to address this gap. Psychological, educational and cross-cultural theories were brought together to investigate the interplay of emotion display and the quality of the teacher-student relationship from a teachers’ perspective and across “cultural-educational” contexts. Given that social interaction, and the mores and norms associated with emotion display are often culturally underpinned, this study explored how university teachers in two so-called “individualistic” countries with different educational systems displayed positive and negative emotions in their teaching and what they perceived as an ideal teacher-student relationship. Australian (N = 15) and German (N = 9) university teachers in teacher education were interviewed. The study revealed that while both groups viewed the open expression of positive emotions as integral to teaching, and negative emotions to be controlled based on their understanding of professionalism, significant group differences were also found. While the Australian teacher educators reported higher and more intense expression of positive emotions, their German counterparts reported more open anger display. Subtle yet noteworthy differences in the TSR quality between the two groups of teachers emerged. The findings of this study have implications for research and practice in international higher education.
Keywords: teacher emotions; emotion display; higher education; teacher-student relationship; cross-cultural comparison:internationalization of higher education